2000
DOI: 10.3171/foc.2000.9.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of the subarachnoid–pleural fistula

Abstract: Subarachnoid–pleural fistula is a rare type of cerebrospinal fluid (CSF) fistula, and there are only several cases reported in the literature. The authors describe a 65-year-old male patient in whom a diagnosis of T7–8 disc herniation had been made. He underwent surgery via a right lateral extracavitary approach. Postoperatively he developed progressive respiratory distress and headache. A chest x-ray film revealed a pleural effusion, and computerized tomography (CT) myelography demonstrated a subarach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Those requiring operative intervention represent an even smaller number. Of all operations performed for compressive discogenic pathologies, the thoracic region comprises only 1.8 % at most [1][2][3][4]. Hott et al suggested a classification of herniations occupying more than 40 % of the spinal canal to be regarded as 'giant' [5].…”
Section: Epidemiology Pathology and Rationale For Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Those requiring operative intervention represent an even smaller number. Of all operations performed for compressive discogenic pathologies, the thoracic region comprises only 1.8 % at most [1][2][3][4]. Hott et al suggested a classification of herniations occupying more than 40 % of the spinal canal to be regarded as 'giant' [5].…”
Section: Epidemiology Pathology and Rationale For Treatmentmentioning
confidence: 99%
“…A review of the literature reveals 44 described cases of massive pleura-dural fistula. It can be observed that 77 % of these cases were caused by trauma of varying aetiologies and only two (4.5 %) of the cases were described as subsequent to post-operative thoracic disc resection [2,9,[14][15][16][17]. Recently, two cases of spontaneous thoracic CSF leakage in the presence of thoracic disc hernias were described [18].…”
Section: Epidemiology Pathology and Rationale For Treatmentmentioning
confidence: 99%
“…A dural‐pleural fistula is a rare CSF fistula that typically occurs following trauma. To the author's knowledge, there are only four other reports in the literature of a dural‐pleural fistula following thoracic spinal surgery 3–6 . Of these, there is only one report in which such a fistula leads to development of opthalmoplegia, as occurred in this patient 5 .…”
Section: Case Reportmentioning
confidence: 80%
“…Although rare, subarachnoid-pleural fistula has been well described following surgery for either tumor resection, 2,4,9,16 discectomy, 14,15 or vertebral fracture. 11,18 Clinical presentation typically includes respiratory signs due to pleural effusion, signs of intracranial hypotension such as orthostatic headache and oculomotor paralysis, and signs of pneumocephalus.…”
Section: Discussionmentioning
confidence: 99%